Nicotine receptor partial agonists for smoking cessation. - Cahill, C; Lindson-Hawley, N; Thomas, K; Fanshawe, T; Lancaster, T (Wiley, 2016)
Can nicotine receptor partial agonists, including cytisine and varenicline, help people to stop smoking? Background When people stop smoking they experience cravings to smoke and unpleasant mood changes. Nicotine receptor partial agonists aim to reduce these withdrawal symptoms and the pleasure people usually experience when they smoke. The most widely-available treatment in this drug type is varenicline, which is available world-wide as an aid for quitting smoking. Cytisine is a similar medication, but is only available in Central and Eastern European countries and through internet sales. Study characteristics We searched for randomised controlled trials testing varenicline, cytisine or dianicline. We found 39 studies of varenicline compared to placebo, bupropion or nicotine patches. We also found four trials of cytisine, one of which compared it to nicotine replacement therapy. We include one trial of dianicline, which is no longer in development, and so not available to use as a quitting aid. To be included, trials had to report quit rates at least six months from the start of treatment. We preferred the strictest available definition of quitting, and results which had been biochemically confirmed by testing blood or bodily fluids.We conducted full searches up to May 2015, although we have also included several key trials published after that date. Key findings From the information we found (27 trials, 12,625 people), varenicline at standard dose more than doubled the chances of quitting compared with placebo. Low-dose varenicline (four trials, 1266 people) roughly doubled the chances of quitting, and reduced the number and severity of side effects. The number of people stopping smoking with varenicline was higher than with bupropion (five trials, 5877 people) or with NRT (eight trials, 6264 people). Based on the evidence so far, we can calculate that varenicline delivers one extra successful quitter for every 11 people treated, compared with smokers trying to quit without varenicline. The most common side effect of varenicline is nausea, but this is mostly at mild or moderate levels and usually clears over time. People taking varenicline appear to have about a 25% increased chance of a serious adverse event, although these include many which are unrelated to the treatment. We also note that more people were lost from the control groups than from the varenicline groups by the end of the trials, which may mean that the count of events in the control groups is lower than it should be. After varenicline became available to use, there were concerns that it could be linked with an increase in depressed mood, agitation, or suicidal thinking and behaviour in some smokers. However, the latest evidence does not support a link between varenicline and these disorders, although people with past or current psychiatric illness may be at slightly higher risk. There have also been concerns that varenicline may slightly increase heart and circulatory problems in people already at increased risk of these illnesses. The evidence is currently unclear whether or not they are caused or made worse by varenicline, but we should have clearer answers to these questions when a further study is published later this year. Quality of the evidence The varenicline studies were generally of high quality, providing evidence that we consider to be reliable and robust. We rate the quality of the evidence comparing varenicline with NRT as moderate quality (we are reasonably confident of the stability of the evidence), since in some of them the participants knew which treatment they were receiving (i.e. non-blinded open-label trials). We judge the evidence from the cytsine trials to be of low quality (we have limited confidence in the evidence), as there are only two trials, with relatively low numbers included.